2015
DOI: 10.1590/1981-863720150001000052959
|View full text |Cite
|
Sign up to set email alerts
|

Impact of malocclusion on oral health-related quality of life of preschool children

Abstract: Objective This study assessed the relationship of dental malocclusion with COHRQoL considering socioeconomic backgrounds and clinical factors. Methods A survey was carried out in Santa Maria, Brazil, during the National Children's Vaccination Day. The sample comprised 478 children aged 12 to 59 months. Fifteen trained and calibrated examiners evaluated the presence of anterior malocclusion traits (AMT) -anterior open bite, overjet and sealing lip. COHRQoL was measured through overall scores of the Brazilian ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
1
0
2
Order By: Relevance
“…Despite not identifying an association with general malocclusion and SOQR, some studies have identified a significant association with open bite. This finding may be related to the fact that-mainly because it is anterior -it is a more noticeable subtype of malocclusion [9,18,19]. In another cross-sectional study, which evaluated preschoolers aged 2-5 years, conducted in Canoas-RS, an association was identified between malocclusion and SOQOL, using the B-ECOHIS [14].…”
Section: Discussionmentioning
confidence: 97%
“…Despite not identifying an association with general malocclusion and SOQR, some studies have identified a significant association with open bite. This finding may be related to the fact that-mainly because it is anterior -it is a more noticeable subtype of malocclusion [9,18,19]. In another cross-sectional study, which evaluated preschoolers aged 2-5 years, conducted in Canoas-RS, an association was identified between malocclusion and SOQOL, using the B-ECOHIS [14].…”
Section: Discussionmentioning
confidence: 97%
“…O principal impacto da má oclusão na qualidade de vida tem sido relatado como sendo nos domínios do bem-estar emocional e social, que compreendem questões relacionadas com componentes estéticos e autoestima, além de reduzir a aceitação social e a qualidade de vida por vias psicossociais. É importante observar que, em relação a seção família, a má oclusão não apresentou impacto na qualidade de vida e isso mostra que a presença desse aspecto clínico na criança pode não estar sendo observada por sua família 18 .…”
Section: Discussionunclassified
“…Esse tipo de anomalia pode ter efeitos funcionais, estéticos ou psicossociais envolvendo a mastigação, a fonação e a oclusão, com impacto negativo na vida diária dos indivíduos afetados. Sua causa se deve a interação entre fatores ambientais, congênitos, morfológicos e biomecânicos 5,6 . Vem sendo observada uma alta prevalência de crianças atópicas com resposta positiva ao teste alérgico, além de apresentarem padrão de respiração bucal.…”
Section: Introductionunclassified